Lost in Lockdown? The Impact of COVID-19 on Chinese International Student Mobility - Yu, Jing (Journal of International Students, 2021)
Due to uneven and hierarchical global context, the United States has been the world’s number one “Educational Hub” (Knight, 2011), leading the internationalization of higher education in multiple forms, the top priority of which lies in international student recruitment and enrollment. However, the COVID-19 pandemic has thoroughly disrupted the traditional mobility experience—a situation that has broader implications for the demographic landscape of US higher education. This article explores how COVID-19 and pandemic-related Sinophobia affect Chinese students’ perspectives on their educational decision-making. Based on Zoom interviews of a sample of 21 Chinese undergraduate students, this study demonstrates that despite the leading role of the US in international education, it is gradually losing appeal to Chinese students due to disillusionment with the romanticized imaginary of the US, anxiety about uncertain policies, and safety concerns. The unidirectional student mobility from mainland China to the US may be interrupted with Singapore and Hong Kong as the emerging destinations.